Synergistic effects of biochar-coated urea and enriched biochar on nitrogen management in sweet corn - SINGH, SHOBHANA; CHATURVEDI, SUMIT; SUPRIYA; DHYANI, V. C. (Journal of Soil and Water Conservation, 2026)
The study was conducted at GBPUAT, Pantnagar, Uttarakhand, during the Kharif season of 2020 to evaluate the effects of novel fertilizers, specifically biochar-coated urea (BCU) and enriched biochar (EB), on sweet corn (Zea mays L. saccharata). The experiment was arranged in a randomized block design with eight treatments, including no nitrogen (N) application control (T1); 100% recommended dose of fertilizer (RDF) through conventional fertilizer + conventional urea (CU) (T2) ); 100% RDF with vermicompost (VC) 4t ha-1+CU (T3); 100% RDF with EB 2t ha-1+BCU (T4); 75% RDF with VC 4t ha-1 +CU (T5); 75% RDF with EB 2t ha-1+BCU (T6); 75% RDF with VC 4t ha-1+CU+micronutrient mixture (T7) and 75% RDF with EB 2t ha-1+BCU micronutrient mixture (T8) all replicated three times. The highest dehusked cob yield and N uptake were achieved with 100% RDF + EB treatment at 2t ha-1+ BCU. This treatment also exhibited the highest N-use efficiency (NUE), outperforming conventional fertilizer applications by 30%. Applying vermicompost (VC) at 4 t/ha + 100% RDF produced comparable results. Additionally, significantly higher total N uptake at harvest was observed with the 100% RDF + EB at 2t ha-1+ BCU treatment. These findings underscore the effectiveness of integrating BCU and EB in enhancing sweet corn yield, N uptake. Hence, these novel fertilizer combinations can contribute to sustainable agricultural productivity and improved soil health.